Chih-chen Wang: the social responsibility of scientists - Gu (顾超), Chao (National science review, 2021)
Abstract Chih-chen Wang is a distinguished biochemist and molecular biologist, and an Academician of the Chinese Academy of Sciences (CAS). From 2008 to 2013, she was a vice chairperson of the National Committee of the Chinese People's Political Consultative Conference (CPPCC). As a young researcher, Wang participated in research on insulin. Since the 1990s, she has been focusing on the study of protein folding, and has initiated a new research area of isomerase and molecular chaperones in China. In this interview, Chih-chen Wang elaborates on the social responsibility of scientists by drawing on both her scientific research and CPPCC experience. In Wang's view, what China really needs are intellectuals with independent thinking and strong social responsibility, who are able to provide the government valuable advice and communicate with the public to increase society's scientific literacy. She also hopes that female scientists can be more confident and gain greater attention and support from society.